Reevaluating Predictors of Extremely Low Birth Weight: The Dominance of Hemoglobin over Maternal Age and the Discovery of 9.25 g/dL as a New Risk Threshold - Ajeng Normala; Hadi Susiarno (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
AbstractObjectives: Extremely Low Birth Weight (ELBW) is a critical factor influencing neonatal morbidity and mortality. Maternal anemia has been linked to negative pregnancy outcomes; the precise hemoglobin threshold for predicting ELBW risk remains poorly defined, especially in low-resource environments.Methods: A cross-sectional observational study was carried out at Ciawi District Hospital between 2019 and 2020. Data from medical records on maternal hemoglobin levels (g/dL) and neonatal birth weights (grams) were extracted for analysis. Statistical methods employed included the Kruskal-Wallis and Mann-Whitney tests, as well as ROC curve analysis.Results: The study comprised 320 cases. The optimal cutoff value for maternal hemoglobin to accurately predict ELBW was identified as 9.25 g/dL (AUC 0.615; p = 0.045). Mothers with hemoglobin levels below this threshold exhibited a 2.1-fold increase in the risk of delivering ELBW infants (p = 0.039). Additionally, the negative predictive value was determined to be 94.05%, indicating that this threshold may serve as a viable screening tool for assessing the risk of ELBW.Conclusion: Maternal hemoglobin levels below 9.25 g/dL are significantly correlated with an elevated risk of ELBW. This threshold may function as an effective early screening parameter for identifying high-risk pregnancies, thereby improving maternal and neonatal health outcomes.Keywords: Birth Weight, ELBW, Hemoglobin, Maternal Anemia, Risk Screening Evaluasi Ulang Prediktor Berat Badan Lahir Sangat Rendah: Dominasi Hemoglobin pada Usia Ibu dan Penemuan 9,25 g/dL sebagai Ambang Risiko Baru AbstrakTujuan: Berat Badan Lahir Sangat Rendah (BBLR) merupakan faktor penting yang memengaruhi morbiditas dan mortalitas neonatal. Anemia ibu telah dikaitkan dengan hasil kehamilan yang negatif. Ambang hemoglobin yang tepat untuk memprediksi risiko BBLR masih belum didefinisikan dengan baik, terutama di lingkungan dengan sumber daya rendah.Metode: Metode yang digunakan dalam penelitian ini adalah studi observasional potong lintang dilakukan di Rumah Sakit Daerah Ciawi antara tahun 2019 dan 2020. Dilakukan analisis data dari catatan medis tentang kadar hemoglobin ibu (g/dL) dan berat badan lahir neonatal (gram). Metode statistik yang digunakan meliputi uji Kruskal-Wallis dan Mann-Whitney, dan analisis kurva ROC.Hasil: Studi ini terdiri atas 320 kasus. Nilai batas optimal hemoglobin ibu untuk memprediksi BBLR secara akurat diidentifikasi sebesar 9,25 g/dL (AUC 0,615; p = 0,045). Ibu dengan kadar hemoglobin di bawah ambang batas ini menunjukkan peningkatan risiko melahirkan bayi ELBW sebanyak 2,1 kali lipat (p = 0,039). Selain itu, nilai prediktif negatif ditetapkan sebesar 94,05%, yang menunjukkan bahwa ambang batas ini dapat berfungsi sebagai alat skrining yang layak untuk menilai risiko ELBW.Kesimpulan: Kadar hemoglobin ibu di bawah 9,25 g/dL berkorelasi signifikan dengan peningkatan risiko ELBW. Ambang batas ini dapat berfungsi sebagai parameter skrining dini yang efektif untuk mengidentifikasi kehamilan berisiko tinggi sehingga meningkatkan hasil kesehatan ibu dan bayi baru lahir.